2014
DOI: 10.5296/jse.v4i2.5242
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at School Enrolment in Ghana: A Statistical Analysis

Abstract: This paper assesses the determinants of school enrolment in Ghana during the period from1970-2012 using data from World Bank Development Indicators.The study employed the Bayesian Moving Average model (BMA) in order to address the issue of model uncertainty. By making use of 28 regressors as possible determinants of school enrolment, the results of the empirical analysis show that percentage of female teachers in the community, number of schools in the community, household expenditure, labour force with primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Notably, a large body of work from various settings around the world has demonstrated that improved, modernized, and better-equipped health facilities can raise the standard of care, strengthen health capacity, and promote positive outcomes (CGD, 2015;Datar, Mukherji, and Sood, 2007;Marrufob, 2007;WHO, OECD, and World Bank, 2018). Similarly, the construction of schools, improvement of infrastructure, and expansion of resources or learning materials can raise access and enrich educational experiences (Ahiakpor, Nunoo, and Alnaa, 2014;Glewwe and Jacoby, 1994;Handa, 2002;Lavy, 1996). Around two-thirds of the country's population lives in rural areas, with farming, animal herding, and fishing being the mainstay of livelihoods for a large percentage of the population.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a large body of work from various settings around the world has demonstrated that improved, modernized, and better-equipped health facilities can raise the standard of care, strengthen health capacity, and promote positive outcomes (CGD, 2015;Datar, Mukherji, and Sood, 2007;Marrufob, 2007;WHO, OECD, and World Bank, 2018). Similarly, the construction of schools, improvement of infrastructure, and expansion of resources or learning materials can raise access and enrich educational experiences (Ahiakpor, Nunoo, and Alnaa, 2014;Glewwe and Jacoby, 1994;Handa, 2002;Lavy, 1996). Around two-thirds of the country's population lives in rural areas, with farming, animal herding, and fishing being the mainstay of livelihoods for a large percentage of the population.…”
Section: Resultsmentioning
confidence: 99%
“…This is an intuitive result that has been reported in a number of previous studies (see e.g. Ahiakpor et al ., 2014), depicting the positive relationship between household expenditure and number of children in developing countries: larger households generally have less money to spend on children’s education, leading to lower enrolment rates and school performance. The size of the effect is higher and more strongly significant for younger children (0–5 years).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, because it can be difficult for owners to provide relevant financial information, the addition of nonfinancial measures is much preferred (Hayat et al, 2019). Furthermore, a variety of writings suggests that the underutilization of higher capacity is a crucial factor that hinders the production growth of several SMEs in Africa (Ahiakpor et al, 2014;Worlu and Granville, 2017). The concept of capacity utilization is quite desirably used in the production of simpler-to-measure tangible products (Worlu and Granville, 2017), which is very characteristic of SME manufacturing firms in Ghana.…”
Section: Effect Of Business Intelligence On Operational Performancementioning
confidence: 99%
“…The concept of capacity utilization is quite desirably used in the production of simpler-to-measure tangible products (Worlu and Granville, 2017), which is very characteristic of SME manufacturing firms in Ghana. While there is quite a plethora of information on capacity utilization, limited surveys have established capacity utilization as a measure of business performance, particularly in the instance of emerging economies (Ahiakpor et al, 2014). There has been some research into the relationship between BI and firm performance (Nuseir et al, 2021;Chen and Lin, 2021;and Rana et al, 2022;Paulino, 2022;Huang et al, 2022;Lateef and Keikhosrokiani, 2022;Yang et al, 2022;Chen and Lin, 2021;Torres et al, 2018).…”
Section: Effect Of Business Intelligence On Operational Performancementioning
confidence: 99%
See 1 more Smart Citation